Hindering and Supporting Factors of Entrepreneurship Implementation for Nurses: A Narrative Review - Christantie EFFENDY; Maryadi MARYADI; Nurdina Wahyu HIDAYATI; Ruby SUSMAWATI (Indonesia Strategic Sustainability, 2023)
Entrepreneurship in the nursing field is still rising giving greater opportunity for these nursing entrepreneurs. However, nurses need to identify the obstacles and the supports so that their businesses will run well and succeed. To identify the hindering and supporting factors for nurses in entrepreneurship. This study was a narrative review with literature research using electronic databases, which included Science Direct and PubMed between 2011-2021. The framework from the European Medical Writers Association developed by Ferrari was used to guide the study From the total of 11 identified and analyzed literatures, there were seven hindering factors (fear; knowledge and skill; prior working culture experience; decision-making policy and regulations; health insurance, colleague jealousy; and unprofessional attitudes) and two supporting factors (knowledge and skills; ability to seek opportunities). Conducting entrepreneurship in nursing still faces several obstacles but also has some supports, and therefore can be done by developing nurses’ self-potentials and professional attitudes.